India's 'poverty of numbers': revisiting measurement issues - Nayyar, Gaurav; Nayyar, Rohini (2016)
The number of "poor" derived by applying price adjustment to an old consumption basket, which is largely what official poverty measures have done, are very different from estimates based on actual consumption baskets that have changed over time. For instance, the share of cereals in household expenditure halved between 1993-94 and 2011-12 in rural areas. In the light of this, we ask if all expenditure would be on food, what percentage of the population would be unable to meet the prescribed calorie requirement? Adding a "minimum" level of expenditure on clothing-bedding-footwear, fuel and light, and conveyance to the "derived" sum of food expenditure provides a second counterfactual. Similarly, the cumulative addition of expenditure on other consumer goods and services provides further counterfactual scenarios.
Keywords: Poverty - India; Poverty